2022
DOI: 10.3390/land11081188
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Evolution Characteristics and Its Driving Mechanism of Land Use/Land Cover Change in Laos from 2000 to 2020

Abstract: Land use/land cover change (LUCC) research is of great significance to land conservation and regional sustainable development. At present, there is a lack of research on the long-term timing of the change process and mechanisms of LUCC that accords with the national level in Laos. Based on the Global Land-Cover product with the Fine Classification System at 30 m (GLC_FCS30) data set as well as economic and social statistical data, the authors analyzed the spatiotemporal regularity and driving mechanism of LUCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…The changing trend of LUCC in Myanmar is similar to that of other Indochina countries. Research by Hu et al [18], Zhang et al [42], and Niu et al [43] in Vietnam, Laos, Cambodia, and other countries also found the phenomenon of shrinking forests, shrubland, and the expansion of impervious surfaces.…”
Section: Lucc and Its Influencing Factorsmentioning
confidence: 99%
“…The changing trend of LUCC in Myanmar is similar to that of other Indochina countries. Research by Hu et al [18], Zhang et al [42], and Niu et al [43] in Vietnam, Laos, Cambodia, and other countries also found the phenomenon of shrinking forests, shrubland, and the expansion of impervious surfaces.…”
Section: Lucc and Its Influencing Factorsmentioning
confidence: 99%
“…The center of gravity model is commonly employed to analyze the spatial relocation of geographical elements during regional development, capturing the changes in spatial elements through the direction, distance, and speed of the center of gravity's migration. In this study, this model was employed to examine the spatial aggregation characteristics and the changing pattern of cropland distribution (Zhang et al 2022b). The equation for the model is shown as equation (5).…”
Section: Center Of Gravity Model and Standard Deviation Ellipsementioning
confidence: 99%
“…Although some scholars have considered analyzing land use changes in urban agglomerations from different levels of administrative divisions (He et al 2022), they failed to break through the geospatial limitations; some scholars have also divided functional are-as from socio-economic and natural resource dimensions (Miao et al 2021), but less consideration has been given to the land use characteristics of the urban agglomerations themselves. Scholars mainly depict the features of land use temporal changes by constructing LULC dynamic attitude models and comprehensive land use index models (Han et al 2021;; the CLUE-S model, landscape pattern index method and geo-information Tupu are employed to track changes in land use temporal and spatial patterns (Bosch et al 2020;Dutta and Das 2019;). Among them, geo-information Tupu (Tang and Li 2020), as a geospatial and temporal analysis methodology, has shown obvious ad-vantages in analysing land use.…”
Section: Introduction:mentioning
confidence: 99%